CYBER SECURITY ANALYSIS OF IOT DEVICES TRANSMITTING DATA IN THE THINGSPEAK PLATFORM CLOUD - DRAGOS-ALEXANDRU ANDRIOAIA (Journal of Engineering Studies and Research)
The IoT platforms have started to be used more and more due to numerous applications in which they can be used. With the growth of devices that transmit data to the cloud of IoT platforms, security challenges have also emerged. The security of IoT platforms can be analysed, identifying vulnerabilities to attacks on each layer of the IoT architecture. In this paper, the authors test, through an active sniffing attack, the cybersecurity of the IoT devices that transmit data to the Cloud of the ThingSpeak platform. Through this attack, it will analyses whether IoT devices send the data to the ThingSpeak platform’s cloud in the clear, without encrypting it.